Features of myocardial deformation in patients with ischemic heart disease with moderate dilatation of cavity of the left ventricle complicated by the myocardial infarction - A. V. Molodan; V. A. Ivashchuk (Patologìâ)
Aims. To explore the features of the myocardial deformation in patients with IHD. Methods and results. 135 patients were included into the study. 60 of them had IHD with moderate left ventricle dilatation not complicated by myocardial infarction. 40 patients had IHD with myocardial infarction in anamnesis, 35 were healthy (comparison group). Primary levels of the myocardial deformation in patients with myocardial infarction were commonly less than in patients without infarction (from 8% up to 11%). In 67% of the analyzed segments decrease of the deformity (strain) by 6–25% as compared with control was detected. Conclusion. Vector analysis of the longitudinal systolic and diastolic left ventricle deformity in patients with IHD with moderate left ventricle dilatation as compared with control was made. Signifi cant differences in all segments of the ventricular septum were found both in systole and diastole.